CHARACTERISTICS OF ECONOMIC GROWTH AND DEVELOPMENT - Boboqulov Sanjar Baxronkulovich; Boyqobilov Ilyos Otabek oʻgʻli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: In this paper, we review the main characteristics of economic growth and development, distinguishing between the two concepts and highlighting their key indicators. Economic growth refers to the quantitative increase in a country’s output, usually measured by gross domestic product (GDP), whereas economic development encompasses broader qualitative aspects, including improvements in living standards, education, health and social equality. We review the drivers of economic growth, such as technological innovation, capital accumulation and labor force expansion, as well as critical factors affecting economic development, including governance, institutions and human capital. The study then discusses the challenges faced by developing countries, such as income inequality and environmental degradation, and provides policy recommendations for promoting both economic growth and development in a balanced manner.